ALTERNATIF STRATEGI PENGEMBANGAN EKSPOR MINYAK SAWIT INDONESIA - Bambang Dradjat; Hamzah Bustomi (School of Business, Bogor Agricultural University (SB-IPB), 2009)
The development of palm oil export from 2000 to 2006 showed the competitiveness position of Indonesia in the world mar ket was fairly good. In order to increase the growth and values of palm oil export, the experts thought that the role of government as regulators and facilitators are very important. The government became the main actor for the export development throuh de/regulation related to the palm oil commodity. The objectives of actors could be achieved by combining strategies (i) encrease capacity of Belawan and Dumai harbours, (ii) reduction/elimination of loan repayment during grace period of revitalization program, (iii) human resource develeopment for both societies and workers with participative funding from Central Government, Local Government, and enterprises, (iv) reduced cost and time in processing land sertification and Hak Guna Usaha (HGU), (v) improved access for farmers to financial institution (bank), (vi) the establishment of harbours in regions based on palm oil production in the region, and (viii) the development of farm roads.